New approaches in teaching listening for ESL and EFL learners - Jurakulova Hurshida (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article describes different interesting and useful ways and innovative methods of teaching listening comprehension skills in a foreign language using a modern approach, and the importance and differences in teaching it in comparison with other language skills. This article may serve as an additional resource for teachers of English in teaching both ESL and EFL students.